INTEGRATED APPROACH TO DESIGNING WORKSTATIONS IN ERGONOMICS - Karamaddin Allabaevich Kutlimuradov (European Science Publishing, 2024)
Requirements for the design, operation and convenience of workstations. Ergonomics includes designing a workplace that meets the needs of the worker. The article talks about research in the design of product design parameters in the ergonomic design of workstations.
Keywords: workstation design, ergonomic design, design parameters, design, environment, protection